Movie as a Helper for Students' Pronunciation in Speaking Skill Class - Yudar, Ratih Saltri; Aditomo, Dionisius Tito; Silalahi, Novia Sariahta (Elsya : Journal of English Language Studies, 2020)
This research aims to deliver how a movie can help students with their pronunciation in English speaking skill. Speaking is one of English skill that has an important role. While speaking, there is a certain aspect that has to be paid attention by people. Pronunciation is an aspect that important in speaking skill. Pronunciation takes a significant role in speaking because it shows anything while someone speaks and other people understanding based on how someone pronounces a word. This study is aimed for students who learn the English language as a foreign language (EFL) to drive the importance this area. With qualitative method, this study hopes to avoid people from misunderstanding what non-English native speakers say. This study’s discussion drives the urgency to teach speaking with the learning activities designed as well as possible to address pronunciation. This study also recommends parties in educational sector to support the use of various teaching media such as videos pictures, realia, television, but particularly movies. This is because a movie is one of the media that can immensely help student’s speaking ability as they actively engage and have fun in imitating the audiovisual feed they receive.